Similar Efficacy Seen with Ultrasound-Guided Injections of PRP or Saline for Epicondylitis - Powers, Jenny (MD Conference Express, 2014)
Platelet-rich plasma (PRP) was not more effective in relieving the pain due to epicondylitis (tennis elbow) compared with saline when each was delivered by ultrasound-guided injection. However, both groups showed significant decreases in pain scores from baseline at 6 months, suggesting to investigators that tendon stimulation may be the actual mechanism behind the observed lesion repair and improvement in pain symptoms.